(untitled) (Innovative professional education, 2025)
The article examines the features of using digital technologies in teaching natural and mathematical sciences in vocational education institutions. The main advantages of digitalization of the educational process are analyzed, including interactive content, access to electronic resources, the use of adaptive platforms, and augmented and virtual reality technologies. A list of modern digital tools that contribute to increasing learning efficiency is provided. The main challenges of implementing digital technologies are considered, and ways to overcome them are proposed. The prospects for further development of digital education in the field of vocational training of students are determined.